INITIAL GROWTH IN MAIZE IN COMPLIANCE OF AZOSPIRILLUM BRASILENSE INOCULATION AND NITROGEN RATES - Oliveira, Elisa Pereira de [UNESP]; Silva, Matheus Gustavo da; Teodoro, Paulo Eduardo (Univ Federal Uberlandia, 2017)
Investigate the effects of the interaction between nitrogen fertilization and inoculation with diazotrophic bacteria becomes important, especially for maize, highly exacting in N. Thus, the aim of this study was to evaluate the initial growth of maize in compliance A. brasilense inoculation and nitrogen rates. The experiment was conducted in a greenhouse, in Mato Grosso do Sul State University, Aquidauana University Unit, between the months of march and April of 2014. It was used completely randomized design in a 2x4 factorial arrangement with four replications. The treatments consisted of the absence and presence of inoculation with A. brasilense and four levels of nitrogen fertilization (0, 25, 50, 100 kg ha(-1) N). At 40 days after sowing the following variables were evaluated: leaf area, plant height, stem diameter, dry mass of shoot and of root. There was interaction between doses of nitrogen and inoculation with A. brasilense for most of the evaluated variables. Inoculation with A. brasilense provides improvements in the establishment and initial development of maize. In the presence of inoculation with A. brasilense, the development of maize increases linearly the administration of the nitrogen doses.
Keywords: Nitrogen fertilization; Diazotrophic bacteria; Inoculant; Zea Mays L